2016
DOI: 10.1161/atvbaha.116.304054
|View full text |Cite
|
Sign up to set email alerts
|

2014 Jeffrey M. Hoeg Award Lecture

Abstract: Monocytes and macrophages are key cells involved in the early progression of atherosclerosis. Transcription factors that control their development in the bone marrow are important therapeutic targets to control the numbers and functions of these cells in disease. This review highlights what is currently known about the transcription factors that are critical for monocyte development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 128 publications
1
35
0
Order By: Relevance
“…Granulocytes (including neutrophils), monocytes and DCs are thought to be produced by granulocyte-monocyte progenitors (GMPs) and monocyte-DC progenitors (MDPs), which are themselves derived from common myeloid progenitors (CMPs) (reviewed in (Zhu et al, 2016). However, recent studies have challenged hierarchical models of hematopoiesis and instead suggested that progenitors make lineage commitment decisions at an earlier stage than previously thought (Notta et al, 2016; Paul et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Granulocytes (including neutrophils), monocytes and DCs are thought to be produced by granulocyte-monocyte progenitors (GMPs) and monocyte-DC progenitors (MDPs), which are themselves derived from common myeloid progenitors (CMPs) (reviewed in (Zhu et al, 2016). However, recent studies have challenged hierarchical models of hematopoiesis and instead suggested that progenitors make lineage commitment decisions at an earlier stage than previously thought (Notta et al, 2016; Paul et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, the most notable distinction is between classical or inflammatory monocytes, which strongly express Ly6C, and non-classical monocytes (including patrolling monocytes), which lack Ly6C (Carlin et al, 2013; Geissmann et al, 2003; Zhu et al, 2016). Classical monocyte fate is specified by the sequential expression of PU.1, IRF8 and Klf4 transcription factors (Zhu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] An inflamed endothelium recruits inflammatory cells, such as monocytes, via the expression of various mediators and chemokines. [4][5][6] This, in addition to the accumulation of cholesterol and smooth muscle cells (SMCs) in the intima, leads to the transformation of monocytes into foam cells, which consume dead cells and lipids. [7][8][9] The atherogenic process involves multiple cell types, that is, endothelial cells (ECs), 10 SMCs, 11 immune cells, 12 and stem/progenitor cells, 13 in which levels of both intracellular and extracellular reactive oxygen and nitrogen species play a fundamental role in vascular cell homoeostasis and eventually affects the development of atherosclerosis.…”
mentioning
confidence: 99%
“…Only during the past 2 years, new monocyte and dendritic cell subsets have been identified [1][2][3] ; essential transcriptional and epigenetic regulators of monocyte 4 and tissue macrophage specification and maintenance 5 have been uncovered; and an old concept of phenotypic transition of vascular smooth muscle cells (SMCs) to phagocytic macrophage-like cells has gained better understanding at the molecular level. 6,7 The diverse roles of monocytes and macrophages in cardiovascular diseases have been highlighted in several interesting reviews published in ATVB, which addressed their origins, fates, and regulation [8][9][10] in diverse settings such as atherosclerosis and associated cardiometabolic disorders, [11][12][13][14][15] aortic aneurysm, 16 and postschemic myocardial injury. 17 Here, I summarize recent original work in those areas published in ATVB during the past 2 years.…”
mentioning
confidence: 99%